Depression of caregivers is significantly associated with depression and hospitalization of hemodialysis patients. Issue 1 (5th July 2021) - Fu, Lili; Wu, Yanfen; Zhu, Aiguo; Wang, Zhihong; Qi, Hualin
Abstract: Introduction: The current study aims to elucidate the relationships of depression of caregivers with depression of hemodialysis patients and determine predictors of hospitalization of hemodialysis patients. Methods: The single‐center, cross‐sectional study consisted of 200 pairs of eligible hemodialysis patients and caregivers from January 2019 to January 2020. Depression was evaluated using Hospital Anxiety and Depression Scale (HADS) questionnaire. Findings: There were 89 hemodialysis patients with depression (44.5%) and 74 caregivers with depression (37.0%). In multi‐variable logistic regression analysis, the hemodialysis patients with depressed caregivers were at increased risk of depression after adjusting for potential confounders (OR = 2.36, p  = 0.04). Depression of hemodialysis patients ( β  = 0.51, p  = 0.00) and depression of caregivers ( β  = 0.36, p  = 0.04) were predictors of hospitalization of hemodialysis patients. Discussion: Depression was prevalent among hemodialysis patients and their caregivers. Depression of caregivers was a risk factor for depression and hospitalization of hemodialysis patients. Implementation of appropriate screening programs and specific interventions for depression of hemodialysis patients and their caregivers is required.